Associations between Motor Competence, Physical Self-Perception and Autonomous Motivation for Physical Activity in Children - Ole Kristian Ensrud-Skraastad; Monika Haga (MDPI AG, 2020)
Research indicates that children and adolescents gradually participate less in physical activity with age. Several factors are associated with children's physical activity levels, such as motor performance, self-perception of athletic competence and motivation to physical activity. To gain a better understanding of the factors of importance for behavior related to an active lifestyle, the purpose of this study was to investigate the association between motor competence, physical self-perception and autonomous motivation and to examine to what extent this association may vary by sex. The sample consisted of 101 children, whose average age was 11.7 years (SD = 0.57), 53 boys and 48 girls. All subjects were measured on motor competence, physical self-perception and autonomous motivation for physical activity. The results indicate a low positive relationship between motor competence and physical self-perception for the entire sample and among girls. There is also a significant correlation between autonomous motivation and physical self-perception. No significant correlations were found between autonomous motivation and motor competence. The association between physical self-perception and autonomous motivation suggests that psychological factors play an important role in children's participation in physical activity.